Um Hermetismo como elemento fundamental do ocidente um paradoxo entre sua necessidade e sua rejeição - Vieira, Otávio Santana (2016)
This dissertation has as object to show the Hermeticism not only as an ancient philosophical movement, but as a current of thought that breaks with the classical Greek rationality, directing him to a religious philosophical view, or a philosophical religiosity through a unification of the philosophical doctrines and Greco-Egyptian religious. The philosophical problems of theoretical are opposed to the problems about the divine and an experience with divinity, in short a “theologi”. The Hermeticism has as its patron and founder the mythical figure of Hermes Trismegistus, who together survived with Platonism, Middle-Platonism, Middle Stoa and Aristotelianism to the average age because some transmission channels. The Hermeticism rises again with greater force and fury in the Renaissance, shaping or presenting a pre-Christian primordial revelation called prisca theologia or ancient theology. Hermeticism became the Renaissance center of a revival or reediting the theological-metaphysical ancient thought that it intended to seek a new way of interpreting Christianity then. Thus was the basis of a generating hermeneutics of meaning and unification, as well as a sponsor of affirmative relations between philosophies and religions, diversity and religious tolerance. It will also be the source of a form of thought called Western Esotericism, working with one of the cultural and present engines in the history of called esoteric current subsequent to the fifteenth century, presenting itself as the most current research in the area as a rejected knowledge in the history of the West. It will be understood as a key element in the sense that it collaborated heavily for the establishment of an imaginary and an episteme in the Renaissance period, while its epistemological structure survived as a form of thought, while it was rejected by the academy. Thus, Hermeticism has, as a form of thought, an extremely complex logic and epistemological constituent and dynamic which can serve us today as an epistemological and hermeneutic relief as occurred in front antiquity to the decline of Greek rationalism and Renaissance front need for reform in Christianity.